Early Life Adversity and Neuropsychiatric Disease: Differential Outcomes and Translational Relevance of Rodent Models - Waters, Renée C.; Gould, Elizabeth (Frontiers in Systems Neuroscience, 2022)
Abstract It is now well-established that early life adversity (ELA) predisposes individuals to develop several neuropsychiatric conditions, including anxiety disorders and major depressive disorder. However, ELA is a very broad term, encompassing multiple types of negative childhood experiences, including physical, sexual and emotional abuse, physical and emotional neglect, as well as trauma associated with chronic illness, family separation, natural disasters, accidents, and witnessing a violent crime. Emerging literature suggests that in humans, different types of adverse experiences are more or less likely to produce susceptibilities to certain conditions that involve affective dysfunction. To investigate the driving mechanisms underlying the connection between early life experience and subsequent disease, neuroscientists have developed several rodent models of ELA including pain exposure, maternal deprivation and limited resources. These studies have also shown that different types of ELA paradigms produce different but somewhat overlapping behavioral phenotypes. In this review, we first investigate types of ELA may be driving different neuropsychiatric outcomes and brain changes in humans. We next evaluate whether rodent models of ELA can provide translationally relevant information regarding links between specific types of experience and changes in neural circuits underlying dysfunction.